Keynote: Abstract Wikipedia - Vrandečić, Denny (Septentrio Conference Series, 2021)
Wikipedia’s vision is a world in which everyone can share in the sum of all knowledge. One of the largest hindrances is the sheer number of languages Wikipedia needs to cover in order to achieve that goal. We want to tackle this problem with a multilingual Wikipedia allowing for content to be shared between language editions. We separate this goal into two parts: creating and maintaining content in an abstract notation within a project called Abstract Wikipedia, and creating a new project called Wikifunctions that can translate this notation to natural language.